Burning material behaviour in hypoxic environments: An experimental study examining a representative storage arrangement of acrylonitrile butadiene styrene, polyethylene bubble wrap, and cardboard layers as a composite system. (18th June 2021) - Bray, Robert John; Barton, John; Madsen, Dan; van Hees, Patrick
Summary: Cone calorimeter and controlled atmosphere cone calorimeter experiments were conducted on various samples. The intent of the tests was to examine the behavior of uniform and composite samples in a range of thicknesses, irradiances, and oxygen concentrations. Single, uniform layers of acrylonitrile butadiene styrene (ABS) were compared to a composite mix, comprising of ABS with a surface layer of cardboard and a secondary layer of polyethylene bubble wrap (intended to represent a potential storage arrangement). The horizontal samples have been tested at irradiances of 25 and 50 kW/m 2 and oxygen concentrations of 20.95%, 17%, and 15% to examine a range of significant variables. Results for the uniform arrangement indicated various correlations, previously observed in the works of others, such as the relationships typically described between applied heat flux, ignitability, heat release rate and the effect of the introduction of hypoxic conditions. However, results were shown to change significantly when samples were arranged to feature composite layers. A hypothesized cause of the behavioral change, namely the soot and char residual introduced from the incomplete combustion of the cardboard layer, highlights further important variables that require consideration in material testing under hypoxic conditions. Such variables, namely specific material behaviors and sample orientation, must be sufficiently captured in the design methodologies of systems reliant upon the introduction of hypoxic conditions. It is concluded that sufficiently capturing a wider range of variables in burning materials under hypoxic conditions will introduce further design resilience and help optimize fire protection/prevention methods.